Pengaruh Kualitas Aktiva Produktif (KAP), Non Performing Financing (NPF) dan Financing to Deposit Ratio (FDR) Terhadap Profitabilitas Bank Umum Swasta Syariah - Khairiyah, Nurul Musfirah; Sakti, Ditto Taruna; Ramli, Ramli (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research was conducted to test the Quality of Earning Asssets (KAP), Non Performing Financing (NPF), and Financing to Deposit Ratio (FDR) in Sharia Private Banks listed on the OJK for the 2015-2021 period. This type of research uses a quantitative approach with data sources, namely secondary data. The population in this research are Sharia Private Banks. The researcher used data analysis techniques with the statistical application of IBM SPSS Statistics 26. The application was used to test Descriptive Statistical Analysis, Classical Assumption Test, Multiple Linear Regression Analysis and carried out Research Hypothesis Testing. The results of the research, the KAP, NPF, and FDR have a simultaneously effect on Profitability. Furthermore, the KAP have a partially negative and significant effect on Profitability, FDR have a partially positive and significant effect on Profitability. Meanwhile, NPF has no partial effect on Profitability.